Recent biotechnological approaches for treatment of novel COVID-19: from bench to clinical trial. (2nd January 2021) - Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Parvin, Najmeh; Gholami, Ahmad; Ramakrishna, Seeram; Omidifar, Navid; Moghadami, Mohsen; Chiang, Wei-Hung; Mazraedoost, Sargol
Abstract: The global spread of the novel coronavirus (SARS-CoV-2) and increasing rate of mortality among different countries has raised the global concern regarding this disease. This illness is able to infect human beings through person-to-person contact at an extremely high rate. World Health Organization proclaimed that COVID-19 disease is known as the sixth public health emergency of international concern (30 January 2020) and also as one pandemic (12 March 2020). Owing to the rapid outbreak of COVID-19 worldwide, health authorities focused on discovery of effective prevention and treatment techniques for this novel virus. To date, an effective drug for reliable treatment of COVID-19 has not been registered or introduced to the international community. This review aims to provide recently presented techniques and protocols for efficient treatment of COVID-19 and investigate its morphology and treatment/prevention approaches, among which usage of antiviral drugs, anti-malarial drugs, corticosteroids, and traditional medicines, biotechnological drugs (e.g. combination of HCQ and azithromycin, remdesivir, interferons, novaferon, interferon-alpha‐1b, thymosin, and monoclonal antibodies) can be mentioned.